PROSEDUR PELAPORAN PPH 21 KARYAWAN TETAP PADA PT X DENGAN MENGGUNAKAN CORETAX - Muniroh, Nawal Shofiyatul; Sucahyati, Diarany (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2025)
Income Tax Article 21 (PPh 21) is one of the primary sources of state revenue from individual employment income. Under Indonesia’s self-assessment system, the responsibility for reporting PPh 21 lies with employers as withholding agents. In line with the digital transformation of tax administration, the Directorate General of Taxes introduced the Core Tax Administration System (Coretax) to simplify the reporting process. This study aims to describe the PPh 21 reporting procedure at PT X using Coretax and identify the obstacles in its implementation. This research adopts a qualitative descriptive method with observation and documentation techniques. The findings indicate that PT X has systematically implemented the PPh 21 reporting procedure, including data collection, tax calculation using the Average Effective Rate (TER), issuance of withholding slips, and submission of periodic tax returns. Despite resulting in zero payable tax, PT X maintained compliance through timely reporting. The use of Coretax was considered beneficial in streamlining the process, though technical issues such as slow response, frequent errors, auto logout, and unsaved data were encountered. In conclusion, PT X has successfully adapted its reporting procedures in line with regulations, but the stability of the Coretax system must be improved to support optimal taxpayer compliance.Keywords: Income Tax Article 21 (PPh 21), Coretax, Reporting Procedure, Effective Average Rate (TER)